Ergonomic Analysis of Garment Industry using Posture Evaluation Index (PEI) in Virtual Environment - Muslim, Erlinda; Nurtjahyo, Boy; Ardi, Romadhani (UI Scholars Hub, 2011)
Ergonomic Analysis of Garment Industry using Posture Evaluation Index (PEI) in Virtual Environment. This research tried to study, in a virtual environment, the ergonomics of four divisions in garment industry: cutting division, sewing division, button division, and finishing division. Variables that influence the working conditions in each division are different; depend on the real situations that happened. The purpose is to assess the real working conditions based on ergonomics study using Posture Evaluation Index (PEI). PEI integrates the scores of low back analysis (LBA), ovako working posture (OWAS), and rapid upper limb assessment (RULA). Analysis phase was done using digital human model in virtual environment that available on Jack 6.0. The results show that the working conditions in garment industry had enough amount of risk that can injured the musculoskeletal system of the workers. This research enriches the body of ergonomics knowledge in Indonesia because it is the first research in Indonesia that applied virtual environment approach to ergonomics analysis in industry.